(untitled) (Communication & Society, 2022)
The present work aims to analyse the meaning of the concept of friendship through the study of the work of the doctor and philosopher Pedro Laín Entralgo. The initial hypothesis of the study is that the concept of friendship has been used instrumentally by social media networks, and that these do not offer the conditions necessary to fully experience true friendship. To verify this, we focused on the study of the psychological dimensions of friendship proposed by the author, identifying a series of variables and conducting an analysis by means of a survey of university students who are active users of the platform. With these results the descriptive statistics were extracted and a nonparametric analysis was performed of the variables to determine if Facebook does in fact offer the conditions necessary for to experience true friendship in its psychological dimensions. As the results show, to experience true friendship on social networks is difficult, given that the nature of the interactions between users of the platform are not appropriate for this experience. In calling this different type of relationship friendship Facebook benefits from an attractive hook which leads users to generate contacts as a form of currency which benefits the business model of the social media platform. The concept of true friendship is altered, deformed and displaced in favour of other types of relationships.